"PP-type" self-assembling peptides with superior rheological properties. Issue 21 (22nd September 2021) - Li, Fangmin; Gao, Lichang; Zhang, Xudong; Wang, Pin; Liu, Yuanxue; Feng, Jinhui; Zhang, Chunxia; Zhao, Chengru; Zhang, Shang
Abstract : Proline terminated "PP-type" self-assembling peptides have better flowability before gel forming and equivalent gel strength after gel forming. Abstract : The ionic-complementary self-assembling peptides discovered by Zhang Shuguang have solution-to-gel (sol–gel) transition capacity and one such peptide RADA16 has been commercialized into hemostatic agents. However, their sol–gel transition ability was not obvious because the peptide aqueous solution with a concentration greater than 1% w/v appeared to be thick and viscous. The current report describes PP-type self-assembling peptides. In addition to the ionic-complementary sequence, they have prolines at both ends of the sequence. This feature has led to better solubility, lower viscosity of the peptide solution, and simplified synthesis and purification processes while maintaining the great gelling performance of the ionic-complementary peptides. The PP-type peptides self-assembled into a well-organized nanofiber scaffold as shown by TEM. Among the PP-type peptides, the PRVDP9 sequence peptide was tested as a hemostatic agent and a mucosal elevating agent. The results were comparable to the classic RADA16. The PP-type self-assembling peptides have superior sol–gel transition ability. Therefore, it is predicted that they will be more suitable to be transported through catheters or endoscopes and have higher commercialization potential as compared with the classic self-assembling peptide sequences.